2021
DOI: 10.1002/aenm.202003119
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in the Semiconducting Oxide Overlayer for Halide Perovskite Solar Cells

Abstract: Halide perovskite solar cells (HPSCs) contain charge transport layers (CTLs) both above and below the photoactive perovskite layer. These semiconducting CTLs are just as important as the perovskite layer to fully realizing the potential of perovskite materials. In particular, semiconducting oxide overlayer materials (SOOMs) are expected to lower costs and provide better long‐term stability compared to the organic semiconducting materials commonly used for the upper layer. However, SOOM‐based HPSCs are currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 182 publications
(218 reference statements)
0
9
0
Order By: Relevance
“…Without any protective layer on the perovskite layer during the sputtering process, energetic particles break down the perovskite structure and induce decomposition to PbI 2 , which adversely affects the operation of the device. [18,30] With organic CTLs on the perovskite layer, organic CTLs not only are damaged by bombardment with the energetic particles but also do not protect the perovskite layer. [36,37] On the other hand, in the case of metal oxide CTLs on the perovskite layer, it is possible to prevent sputtering damage without a buffer layer, maintaining the photovoltaic performance of the device.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without any protective layer on the perovskite layer during the sputtering process, energetic particles break down the perovskite structure and induce decomposition to PbI 2 , which adversely affects the operation of the device. [18,30] With organic CTLs on the perovskite layer, organic CTLs not only are damaged by bombardment with the energetic particles but also do not protect the perovskite layer. [36,37] On the other hand, in the case of metal oxide CTLs on the perovskite layer, it is possible to prevent sputtering damage without a buffer layer, maintaining the photovoltaic performance of the device.…”
Section: Resultsmentioning
confidence: 99%
“…Oxide CTLs are thermally stable as well as physically durable, thereby enabling to prevent sputtering damages. [30] Therefore, a promising semitransparent PSC structure is the BTE/n-type oxide/perovskite halide/p-type oxide/TTE structure without a buffer layer. The p-type oxide layer on the perovskite layer acts as a p-type CTL as well as a buffer layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CuO, MoO 3 , and NiO x are inorganic HTLs that have shown excellent performance in fabricating stable and efficient PSCs. [231][232][233][234][235] Several QDs were found to be very effective in enhancing the PCE stability. The Cu 1.8 S modified HTL could enhance hole extraction at the PS/HTL interface and suppress carrier recombination.…”
Section: Znsementioning
confidence: 99%
“…The laboratory certified efficiency of PSK single junction cells has increased from 3.8% [97] in 2009 to 25.5% [50,98] currently, making it an ideal top-cell for TSC due to its bandgap tunability [99][100][101], high defect tolerance [102,103], high absorption coefficient [104], and steep absorption edge [105][106][107]. The current study found that mirror-like PSK cells exhibit superior PV performance [108][109][110][111], contrary to the robust light trapping of pyramid-textured Si [112,113].…”
Section: Single Junction Solar Cellmentioning
confidence: 99%